2000
DOI: 10.1038/sj.cgt.7700094
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity is induced in murine colon carcinoma cells by the expression of interleukin-12 or interleukin-18, which activate type 1 helper T cells

Abstract: We investigated the antitumor effects induced by the production of interleukin-12 (IL-12) or IL-18, which influence the function of T helper type 1 cells, in murine colon carcinoma cells (Colon 26). Retrovirally transduced cells with IL-12 genes that encoded both p35 and p40 (Colon 26/IL-12) lost their tumorigenicity when inoculated subcutaneously or intraperitoneally into syngeneic immunocompetent mice. Moreover, the mice that had rejected the Colon 26/IL-12 cells generated protective immunity to wild-type

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
1
34
2
Order By: Relevance
“…1 Osaki et al 18 reported a synergistic antitumor effect of IL-18 gene transduction and recombinant IL-12 administration. However, most of these earlier studies employed retrovirus, [18][19][20][21] or adenovirus vectors, 22,23 while cationic liposome was also used in some studies. 24 In the present study, IL-12 and IL-18 genes were trans-ferred into B16 solid tumors via electroporation, as a novel approach to gene therapy of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1 Osaki et al 18 reported a synergistic antitumor effect of IL-18 gene transduction and recombinant IL-12 administration. However, most of these earlier studies employed retrovirus, [18][19][20][21] or adenovirus vectors, 22,23 while cationic liposome was also used in some studies. 24 In the present study, IL-12 and IL-18 genes were trans-ferred into B16 solid tumors via electroporation, as a novel approach to gene therapy of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] IL-18 was shown to induce the immune defense against tumors in various animal models. [25][26][27] We hypothesized that transfection of IL-18 gene into the tumor may augment the production of tumor-suppressive cytokines (IFN-␥ and IL-2), rescue the CTL against the tumor cells, enhance NK cell activity, and thus profoundly potentiate Fab-SEA-based cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The p19 and p35 genes were linked to the p40 gene using an internal ribosomal entry site (IRES) to construct an expression vector with pcDNA3 (Invitrogen, Carlsbad, CA): for IL-12, p35-IRES-p40; for IL-23, p19-IRES-p40; and for p40, IRES-p40. COS-7 cells were transfected with these vectors using Lipofectin reagent (Invitrogen) and cell-free supernatants were collected after 48 hr.…”
Section: Expression Of Cytokines and Cytokine Production Assaymentioning
confidence: 99%